2020
DOI: 10.3390/cancers12123823
|View full text |Cite
|
Sign up to set email alerts
|

An Amplified Fatty Acid-Binding Protein Gene Cluster in Prostate Cancer: Emerging Roles in Lipid Metabolism and Metastasis

Abstract: Treatment for early stage and localized prostate cancer (PCa) is highly effective. Patient survival, however, drops dramatically upon metastasis due to drug resistance and cancer recurrence. The molecular mechanisms underlying PCa metastasis are complex and remain unclear. It is therefore crucial to decipher the key genetic alterations and relevant molecular pathways driving PCa metastatic progression so that predictive biomarkers and precise therapeutic targets can be developed. Through PCa cohort analysis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 133 publications
0
23
0
1
Order By: Relevance
“…Reprogramming of tumor metabolism played a signi cant role in tumor metastasis [21,22]. Plenty of tumor metabolism related genes had been discovered [23][24][25][26]. Among the H-DEGs, iron metabolism related genes including GOT1 and CP [27,28], glutamine metabolism related gene GOT1 [29], pyruvate metabolism related gene PC [30], proline metabolism related gene ALDH4A1 [31], and so on were found in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Reprogramming of tumor metabolism played a signi cant role in tumor metastasis [21,22]. Plenty of tumor metabolism related genes had been discovered [23][24][25][26]. Among the H-DEGs, iron metabolism related genes including GOT1 and CP [27,28], glutamine metabolism related gene GOT1 [29], pyruvate metabolism related gene PC [30], proline metabolism related gene ALDH4A1 [31], and so on were found in this study.…”
Section: Discussionmentioning
confidence: 58%
“…FABP4, FABP5, FABP8, FABP9, and FABP12 loci were found in a commonly amplified region within the chromosome 8 (8q21.13), frequently observed in human PCas mets. In line with this, increased mRNA levels of FABP 4, 8, 9, and 12 were associated with increased Gleason score and PCa recurrence (90). In 2020, Liu and coworkers also demonstrated that FABP12 promotes EMT and PCa cell motility, at least in part, through a PPARg-dependent pathway (113), while FABP9 suppression inhibits PC3 cell invasive potential in PPARgindependent manner (86).…”
Section: Alterations In Fa Transportmentioning
confidence: 75%
“…FABP5 is the most characterized and highly expressed FABP in human PCas and cell lines, especially in CRPC cells (81)(82)(83)(84)(85)(86)(87)(88). Different mechanisms account for FABP5 upregulation, including a positive feedback loop mediated by include proliferator-activated receptors (PPAR) PPARb/d (89), CpG island hypomethylation (85), and gene amplification (90). The latter is highly frequent in advanced CRPC (88).…”
Section: Alterations In Fa Transportmentioning
confidence: 99%
“…Consequently, novel prognostic biomarkers and treatments for BLCA need to be identified to improve patient prognosis. Accumulating studies have suggested that lipid metabolism dysregulation was involved in development and progression of various cancers, including lung cancer [ 18 ], prostate cancer [ 19 ], gastric carcinoma [ 20 ], and BLCA [ 13 ]. Despite the crucial role of lipid metabolism in BLCA, studies about the relationship between lipid metabolism and BLCA prognosis are rare.…”
Section: Discussionmentioning
confidence: 99%